Associations of retinal microvascular caliber with large arterial function and structure: A population‐based study of 11 to 12 year‐olds and midlife adults. (25th June 2020) - Liu, Mengjiao; Lycett, Kate; Wong, Tien Yin; Grobler, Anneke; Juonala, Markus; He, Mingguang; Dwyer, Terry; Burgner, David; Wake, Melissa
Abstract: Objective: We examined associations between retinal microvascular and large arterial phenotypes to explore relationships between the micro‐ and macro‐vasculature in childhood and midlife. Methods: Participants were 1288 children (11‐12 years, 50.9% female) and 1264 adults (mean age 44 years, 87.6% female) in a cross‐sectional population‐based study. Exposures were retinal arteriolar and venular caliber quantified from retinal images. Outcomes included arterial function (pulse wave velocity; carotid arterial elasticity) and structure (carotid intima‐media thickness). Multivariable regression models were performed adjusting for age, sex, and family socioeconomic position. Results: In children, one standard deviation wider arteriolar caliber was associated with slower pulse wave velocity (−0.15 SD, 95% CI −0.21, −0.09) and higher elasticity (0.13 SD, 95% CI 0.06, 0.20); per SD wider venular caliber was associated with faster pulse wave velocity (0.09 SD, 95% CI 0.03, 0.15) and lower elasticity (−0.07 SD, 95% CI −0.13, −0.01). The size of adult associations was approximately double. Wider arteriolar caliber was associated with smaller carotid intima‐media thickness (−0.09 SD, 95% CI −0.16, −0.03) in adults but not children. Venular caliber and carotid intima‐media thickness showed little evidence of association. Conclusions: Narrower retinal arterioles and wider venules are associated with large arterial function as early as mid‐childhood. Associations strengthen by midlife and also extend to arterial structure, although effect sizes remain small.